If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -13 = 4x + -2 Reorder the terms: -13 + 5x = 4x + -2 Reorder the terms: -13 + 5x = -2 + 4x Solving -13 + 5x = -2 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -13 + 5x + -4x = -2 + 4x + -4x Combine like terms: 5x + -4x = 1x -13 + 1x = -2 + 4x + -4x Combine like terms: 4x + -4x = 0 -13 + 1x = -2 + 0 -13 + 1x = -2 Add '13' to each side of the equation. -13 + 13 + 1x = -2 + 13 Combine like terms: -13 + 13 = 0 0 + 1x = -2 + 13 1x = -2 + 13 Combine like terms: -2 + 13 = 11 1x = 11 Divide each side by '1'. x = 11 Simplifying x = 11
| 5x-13=4x-2•/.2 | | 2/3(2-x)-1/2(2x+5)=5/6(-x-3) | | Y^10/Y^6 | | 22.75=20c+5.75 | | (26n-6)=13n | | v^7-v^5=c | | v^7-v^5-c=0 | | 7x^2+20=6 | | 8m+2=16m+2 | | 12/2(3)*2 | | 12/2(3)x2 | | x+2x+3x=50 | | 4-3ln(x+5)=1 | | 2x+40.3=-6x-40.3 | | b+6=26 | | f(x+h)=2x^2+5x+8 | | 8x^2+27x-63=0 | | 0=-16t^2-200 | | 3/p=9/7 | | 3k^2+30k=0 | | 9x^2-7x-9=0 | | e^2x-4+3=2 | | 6p+22=0 | | 5q+2=37 | | 4x^1/3=16 | | (26-6)=13n | | 2Y+24(24)=89 | | 16x^2+20x-200=0 | | 5/9u=20 | | 6z+18=5z+3 | | -9a=1 | | 6.3=(x*9.36)+(y*5.04) |